Frequency of Pelvic Pain and Bleeding per Vaginum in First Trimester of Pregnancy in a Tertiary Care Hospital of Karachi - Mehreen Iqbal; Syeda Rabia; Samreen Fakeer Muhammad (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Objective: The objective of this study was to determine the frequency of pelvic pain and per vaginal bleeding, in the first trimester of pregnancy. Methods: A total of 150 pregnant women 18 to 35 years in first trimester were recruited in this cross- sectional study, conducted from  July  2015  to  July  2016.  Non-probability  sampling  technique  was   used to collect the data. The collected information from  patients  were  entered  in  pre-designed  proforma after taking informed consent. Data was analysed by using SPSS version 20. Results: The average age of the patients was 26.33 ± 4.23 (range 18-35) years. Frequency of pelvic pain and per vaginal bleeding in first  trimester  of  pregnancy  was  observed  in  29.33%  (44/150)  and 12% (18/150) respectively. Stratification analysis was performed and it was observed that rate of pelvic   pain and per vaginal bleeding was not  statistically  significant  among  different  age  groups.  Rate  of  pelvic pain was significantly high in women with primigravida as compare to multigravida (p=0.003). Conclusion: We found in our sample a significant number of women  experiencing  pelvic  pain  and  vaginal bleeding in first trimester of their pregnancy. The practitioner must employ sound clinical and diagnostic skills in the management of the patient as early pregnancy complications  can  cause  sig-  nificant distress for some women and their partners.